Application of Low-Pressure Tanks in Fire Protection Systems - Kańtoch, Robert; Gnatowska, Renata; Sosnowski, Marcin (Instal, 2026)
This paper presents the concept of a vacuum-assisted oxygen reduction system designed for fire protection in confined spaces. Different valve configurations – including diameter, position, and opening mode – were analyzed to assess their impact on the rate of oxygen concentration reduction. The results indicate that a centrally positioned DN40 valve enables very rapid oxygen depletion, reaching a concentration level of 15.4% by volume in less than one second after full valve opening. These findings demonstrate a significant potential of the system as a fire prevention method, particularly in smaller enclosed facilities where fast response and energy-efficient operation are crucial. The analyzed concept, referred to as the Vacuum Oxygen Reduction System (VORS), is characterized by short reaction times, low energy demand, and the possibility of implementation in both stationary and mobile systems. It may represent an attractive alternative to conventional inert gas systems and opens perspectives for further development in engineering practice.